Design and Application of a Low pH Upflow Biofilm Sulfidogenic Bioreactor for Recovering Transition Metals From Synthetic Waste Water at a Brazilian Copper Mine - Santos, Ana L.; Johnson, D. Barrie (Frontiers in Microbiology, 2018)
A sulfidogenic bioreactor, operated at low pH (4 – 5), was set up and used to remove transition metals (copper, nickel, cobalt and zinc) from a synthetic mine water, based on the chemistry of a moderately acidic (pH 5) drainage stream at an operating copper mine in Brazil. The module was constructed as an upflow biofilm reactor, with microorganisms immobilized on porous glass beads, and was operated continuously for 462 days, during which time the 2 L bioreactor processed > 2,000 L of synthetic mine water. The initial treatment involved removing copper (the most abundant metal present) off-line in a stream of H2S-containing gas generated by the bioreactor, which caused the synthetic mine water pH to fall to 2.1. The copper-free water was then amended with glycerol (the principal electron donor), yeast extract and basal salts, and pumped directly into the bioreactor where the other three transition metals were precipitated (also as sulfides), concurrent with increased solution pH. Although some acetate was generated, most of the glycerol fed to the bioreactor was oxidized to carbon dioxide, and was coupled to the reduction of sulfate to hydrogen sulfide. No archaea or eukaryotes were detected in the bioreactor microbial community, which was dominated by acidophilic sulfate-reducing Firmicutes (Peptococcaceae strain CEB3 and Desulfosporosinus acididurans); facultatively anaerobic non-sulfidogens (Acidithiobacillus ferrooxidans and Actinobacterium strain AR3) were also found in small relative abundance. This work demonstrated how a single low pH sulfidogenic bioreactor can be used to remediate a metal-rich mine water, and to facilitate the recovery (and therefore recycling) of target metals. The system was robust, and was operated empirically by means of pH control. Comparison of costs of the main consumables (glycerol and yeast extract) and the values of the metals recovered showed a major excess of the latter, supporting the view that sulfidogenic biotechnology can have significant economic as well as environmental advantages over current approaches used to remediate mine waters which produce secondary toxic wastes and fail to recover valuable metals.